1998
DOI: 10.1107/s0021889897012181
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Dislocation-Induced Anisotropic Line Broadening in Rietveld Refinements Using a Voigt Function. II. Application to Neutron Powder Diffraction Data

Abstract: In paper I [Wu et al. (1998). J. Appl. Cryst. 31,[356][357][358][359][360][361][362] an approach was developed to the problem of modelling dislocation-induced X-ray or neutron-diffraction-line broadening. This paper applies those findings to the Rietveld refinement of the neutron powder diffraction profiles of deuterium-cycled LaNi5 and/%PdD0.66. These interstitially modified materials exhibit, respectively, strong and weak anisotropic strain broadening. The broadening in LaNi5 is consistent with a dislocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 18 publications
5
40
2
Order By: Relevance
“…They are one order of magnitude higher than those usually observed in plastically deformed metals, such as zirconium, for which a value of 4 Â 10 10 cm À2 was determined from X-ray powder diffraction data (Klimanek & Kuz Ïel, 1989). Surprisingly, the value of 4.8 Â 10 12 cm À2 as determined for LaNi 5 by Wu et al (1998) from neutron powder diffraction data is still higher by an order of magnitude. Dislocation densities of this magnitude have not been observed in any of our samples and are in strong contrast with those observed in plastically deformed metals.…”
Section: à2mentioning
confidence: 97%
See 2 more Smart Citations
“…They are one order of magnitude higher than those usually observed in plastically deformed metals, such as zirconium, for which a value of 4 Â 10 10 cm À2 was determined from X-ray powder diffraction data (Klimanek & Kuz Ïel, 1989). Surprisingly, the value of 4.8 Â 10 12 cm À2 as determined for LaNi 5 by Wu et al (1998) from neutron powder diffraction data is still higher by an order of magnitude. Dislocation densities of this magnitude have not been observed in any of our samples and are in strong contrast with those observed in plastically deformed metals.…”
Section: à2mentioning
confidence: 97%
“…It can be shown that P 9 3M. We have determined the values of P independently for each pro®le from the ratio between the Lorentz ( L ) and Gauss ( G ) integral breadths of the diffraction pro®les according to the approximation proposed by Wu et al (1998):…”
Section: Individual Profile Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisotropic crystallite shape are a delicate phenomenon [26] which has been treated by special elegance in the case of ZnO nanoparticles [23]. Finally, anisotropic strain broadening is a general feature of powder patterns [43][44][45][46][47][48][49][50][51][52][53][54][55][56], which is generally related to dislocations and the elastic properties of crystals. In the present work a few typical examples are reviewed where the microstructure of nanocrystalline materials has been characterized by the method of XLPA.…”
Section: Introductionmentioning
confidence: 99%
“…The broadening can be qualitatively modeled by empirical models, such as the general model proposed by [Stephens (1999)]. Quantitative modeling allowing also the determination of dislocation type and density [Wu et al (1998[Wu et al ( ), Č erný et al (2000] was possible by applying the theory of Krivoglaz [Krivoglaz (1969)] modified for hexagonal symmetry in [Klimanek andKužel (1988, 1989)]. …”
Section: Anisotropic Line Broadeningmentioning
confidence: 99%